2019
DOI: 10.1016/j.envres.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Ambient ozone and fine particulate matter exposures and autism spectrum disorder in metropolitan Cincinnati, Ohio

Abstract: Background: Epidemiological studies report fairly consistent associations between various air pollution metrics and autism spectrum disorder (ASD), with some elevated risks reported for different prenatal and postnatal periods. Objectives:To examine associations between ASD and ambient fine particulate matter (PM 2.5 ) and ozone concentrations during the prenatal period through the second year of life in a casecontrol study.Methods: ASD cases (n=428) diagnosed at Cincinnati Children's Hospital Medical Center w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…Particulate matter (PM), and especially its fine fraction (PM 2.5 ), existing in the atmosphere is considered to cause severe and different toxic effects on humans, including respiratory (Kowalska et al, 2019) and cardiovascular diseases (Du et al, 2019), nephrotoxicity (Hsu et al, 2005), diabetes (Lao et al, 2019), fetal distress in pregnant women (Liu et al, 2019), allergy (Dedele et al, 2019), autism (Kaufman et al, 2019), decreased fertility (Xia et al, 2019), and cancer (Santibáñez-Andrade et al, 2017). Eye irritation, dry throat, runny nose, sneezing, cough, tiredness, irritability, difficulty concentrating, headache, dizziness, and skin irritation are other less serious, indeed annoying side effects of human exposure to PM (Nezis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter (PM), and especially its fine fraction (PM 2.5 ), existing in the atmosphere is considered to cause severe and different toxic effects on humans, including respiratory (Kowalska et al, 2019) and cardiovascular diseases (Du et al, 2019), nephrotoxicity (Hsu et al, 2005), diabetes (Lao et al, 2019), fetal distress in pregnant women (Liu et al, 2019), allergy (Dedele et al, 2019), autism (Kaufman et al, 2019), decreased fertility (Xia et al, 2019), and cancer (Santibáñez-Andrade et al, 2017). Eye irritation, dry throat, runny nose, sneezing, cough, tiredness, irritability, difficulty concentrating, headache, dizziness, and skin irritation are other less serious, indeed annoying side effects of human exposure to PM (Nezis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The review found evidence for associations between prenatal exposure to PM 2:5 and ASD (Lam et al 2016). Additional studies have been published since this review that have found positive associations between prenatal and/or early life PM 2:5 exposure and ASD (Kaufman et al 2019;Jo et al 2019;McGuinn et al 2020).…”
Section: Discussionmentioning
confidence: 81%
“…2016 ). Additional studies have been published since this review that have found positive associations between prenatal and/or early life exposure and ASD ( Kaufman et al. 2019 ; Jo et al.…”
Section: Discussionmentioning
confidence: 99%
“…We found 12 studies (9 case-control and 3 cohort studies) investigating the association between the risk of ASD onset and maternal exposure to PM (PM 2.5 and PM 10 ) during pregnancy and in the first years of the child's life and the risk ASD onset (Table 1). The case-control studies showed a positive association between PM exposure (especially PM 2.5 ) during pregnancy or early life and ASD [23][24][25][26][27][28][29][30][31], while the cohort studies demonstrated a less significant relationship.…”
Section: Association Between Pm and Asdmentioning
confidence: 99%